2007
DOI: 10.1002/chin.200704148
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of Acyclic and Macrocyclic Uracil Derivatives with Quaternized Nitrogen Atoms in Spacers.

Abstract: Antibacterial and antifungal activities of 13 members of the title series are presented. In particular, (Ib) and (II) show significant bacteriostatic, fungistatic, bactericidal, and fungicidal activity. -(SEMENOV*, V. E.; VOLOSHINA, A. D.; TOROPTZOVA, E. M.; KULIK, N. V.; ZOBOV, V. V.; GINIYATULLIN, R. K.; MIKHAILOV, A. S.; NIKOLAEV, A. E.; AKAMSIN, V. D.; REZNIK, V. S.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Table 2 revealed that the uracil-anisaldehyde Schiff base (UB) showed relatively higher antimicrobial activities than uracil-benzaldehyde Schiff base (UA). That could be attributed to the higher adsorption tendency of the oxygen atom in the methoxy groups (-O-CH 3 ) due to the lone pair of electrons of oxygen atom [26,27].…”
Section: Biological Activity Of the Synthesized Cationic Schiff Base mentioning
confidence: 99%
“…Table 2 revealed that the uracil-anisaldehyde Schiff base (UB) showed relatively higher antimicrobial activities than uracil-benzaldehyde Schiff base (UA). That could be attributed to the higher adsorption tendency of the oxygen atom in the methoxy groups (-O-CH 3 ) due to the lone pair of electrons of oxygen atom [26,27].…”
Section: Biological Activity Of the Synthesized Cationic Schiff Base mentioning
confidence: 99%
“…The target compounds 3 were synthesized by starting from substituted benzyl bromide 4 and diamines 5 a – c , the latter of which were obtained from dibromides 6 and ethylamine. This step was described elsewhere . Scheme shows the steps leading to bisamines 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Initial compounds 5 a–c : The syntheses of initial compounds 1,3‐bis(4‐ethylaminobutyl)‐6‐methyluracil ( 5 a ), 1,3‐bis(5‐ethylaminopentyl)‐6‐methyluracil ( 5 b ), and 1,3‐bis(6‐ethylaminohexyl)‐6‐methyluracil ( 5 c ) were reported previously …”
Section: Methodsmentioning
confidence: 99%
“…Minimal inhibitory concentrations (MICs) were estimated by conventional dilution methods for bacteria and fungi [57,58]. The antibacterial and antifungal assays were performed in Hottinger broth (HiMedia Laboratories Pvt.…”
Section: Fluorescencementioning
confidence: 99%